2016
DOI: 10.1038/srep34563
|View full text |Cite
|
Sign up to set email alerts
|

Successful weight reduction and maintenance by using a smartphone application in those with overweight and obesity

Abstract: A discrepancy exists with regard to the effect of smartphone applications (apps) on weight reduction due to the several limitations of previous studies. This is a retrospective cohort study, aimed to investigate the effectiveness of a smartphone app on weight reduction in obese or overweight individuals, based on the complete enumeration study that utilized the clinical and logging data entered by Noom Coach app users between October 2012 and April 2014. A total of 35,921 participants were included in the anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
106
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(119 citation statements)
references
References 44 publications
12
106
1
Order By: Relevance
“…Our results agree with similar results obtained in another study14. One of the variables playing an important role in this analysis was the location of the user, which allowed us to keep track of the different diets, lifestyles, ethnicities and different climatic conditions of the distinct locations.…”
Section: Discussionsupporting
confidence: 90%
“…Our results agree with similar results obtained in another study14. One of the variables playing an important role in this analysis was the location of the user, which allowed us to keep track of the different diets, lifestyles, ethnicities and different climatic conditions of the distinct locations.…”
Section: Discussionsupporting
confidence: 90%
“…e scale and duration of this study contribute to the growing evidence base that mobile applications may be a useful tool in combating obesity at a population level with the distinct advantage of being widely accessible, relatively low cost, and without the constraint of face-to-face interaction [5]. is is the largest observational study of a mobile application for weight loss with the largest similar study reporting on approximately 36,000 individuals [17]. Our study differs significantly by adding the hybrid approach use of a wireless home scale and specific nutrition plan.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent report concluded that 21 of 25 (84%) digital diabetes prevention and management programs (addressing modification of diet, activity, and/or weight) used live human counseling as a part of the intervention. In fact, one of the most intensively studied uses of AI in an ILI includes live human counseling in addition to AI . Use of streaming media may be another answer to this conundrum, and it is more fully developed than AI.…”
Section: Summary and Future Directionsmentioning
confidence: 99%